Redo ileocolic resection in Crohn's disease – does time passed since previous surgery matter?. (10th January 2022) - Freund, Michael R.; Kent, Ilan; Horesh, Nir; Smith, Timothy; Wexner, Steven D.
Abstract: Aim: Surgical resection for Crohn's disease (CD) remains noncurative, therefore recurrence is a significant problem. Although numerous factors affecting surgical outcomes in redo ileocolic resection have been previously described, no study has considered the relation between the interval of time from initial ileocolic resection to the redo procedure and its effect on surgical outcomes. The aim of this study was to explore this relationship. Method: A retrospective review of all adult patients undergoing redo ileocolic resection for CD between 2011 to 2020 was conducted. Patients were divided into two groups based on time from initial ileocolic resection. Patients operated within 10 years of their initial surgery (≤10 years) were assigned to the early group, while patients operated >10 years after initial surgery were allocated to the late group. Primary outcome was the 30‐day postoperative major complication rate. Results: Fifty‐eight patients underwent redo ileocolic resection, 24 in the early group and 34 in the late group. Apart from older median age in the late group (56 vs. 46.5 years, p  = 0.026), the groups were similar for patient factors, disease site and behaviour, use of immune‐suppressing medication and procedural factors. Significant differences in 30‐day postoperative morbidity included longer length of stay (6 vs. 5 days, p  = 0.035), a higher major complication rate (23.5% vs. 4.1%, p  = 0.04) and higher readmission rate (26.4% vs. 4.1%, p  = 0.035) in the late group. The overall complication rate remained nonsignificant (37.5% vs. 61.8%, p  = 0.1). Conclusions: Redo ileocolic resection, when performed >10 years from the initial ileocolic resection, may be associated with increased morbidity, specifically higher rates of major postoperative complications, a longer length of stay and more readmissions.